2012
DOI: 10.1186/1479-5876-10-7
|View full text |Cite
|
Sign up to set email alerts
|

c-KIT receptor expression is strictly associated with the biological behaviour of thyroid nodules

Abstract: BackgroundA large amount of information has been collected on the molecular tumorigenesis of thyroid cancer. A low expression of c-KIT gene has been reported during the transformation of normal thyroid epithelium to papillary carcinoma suggesting a possible role of the gene in the differentiation of thyroid tissue rather than in the proliferation. The initial presentation of thyroid carcinoma is through a nodule and the best way nowadays to evaluate it is by fine-needle aspiration (FNA). However many thyroid F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 29 publications
8
38
0
Order By: Relevance
“…It was previously reported that hsa-miR-221 and hsa-miR-222 were upregulated in PTC tissues (14)(15)(16)(17)(18), consistent with our results, while hsa-miR-15a and hsa-miR-299 were downregulated (19). At the mRNA levels, MET was demonstrated to be upregulated (20) and KIT was downregulated (21,22). In thyroid oncocytic tumors, ITGAV was found to be upregulated (23).…”
Section: Discussionsupporting
confidence: 92%
“…It was previously reported that hsa-miR-221 and hsa-miR-222 were upregulated in PTC tissues (14)(15)(16)(17)(18), consistent with our results, while hsa-miR-15a and hsa-miR-299 were downregulated (19). At the mRNA levels, MET was demonstrated to be upregulated (20) and KIT was downregulated (21,22). In thyroid oncocytic tumors, ITGAV was found to be upregulated (23).…”
Section: Discussionsupporting
confidence: 92%
“…Several transcripts, previously demonstrated to exhibit strong expression level changes in the FTC and PDTC, such as TIMP1, c-MET and c-KIT [20, 42], were included for the correlation analysis. Probes were designed and synthesized by NanoString nCounterTM technologies.…”
Section: Methodsmentioning
confidence: 99%
“…Starting from 69 FNAC smears with known c-KIT expression levels, previously described in our paper [17], we here investigated PAX8 and TTF-1 mRNA expression levels. Moreover, we overexpressed c-KIT in a PTC cell line to perform functional studies.…”
Section: Introductionmentioning
confidence: 99%